The larva of the genus Misagria Kirby, 1889 (Odonata: Libellulidae) - Fleck, Günther; Neiss, Ulisses G. (Zootaxa, 2019)
The ultimate stadium of Misagria parana Kirby, 1889 is described and illustrated for the first time based on reared material. The larva was hitherto unknown for the genus. Based on M. parana, M. divergens Westfall, 1992 and M. cf. calverti a larval generic diagnosis is given. Larva of the genus Misagria Kirby, 1889 is briefly compared to the strongly similar larvae of the Neotropical genera Cannaphila Kirby, 1889, and Dasythemis Karsch, 1889. Larvae of Misagria can be separated from those of Dasythemis by the number of palpal setae (seven in Misagria vs four in Dasythemis) and by the shape of ventral tarsal setae (trifid setae present in Misagria), and from those of Cannaphila by the number of palpal setae (seven vs five or six) and the chaetotaxy of middorsal abdominal segments (segments three to nine with a diffuse clump of long setae in Misagria vs no diffuse clump in Cannaphila).